KEMATANGAN EMOSI DAN ORIENTASI BERKARIR TERHADAP KEPUTUSAN MENIKAH PADA MAHASISWI - Rosalina, Mia; Ekasari, Agustina (SOUL : Jurnal Pemikiran dan Penelitian Psikologi, 2015)
The study aims to determining whether emotional readiness and career oriented correlated with and influenced marital decision. The subjects were 41 psychology students in Universitas Islam ?45? Bekasi. Data were collected using observation, interview, emotional readinnes scale, career oriented scale, and marital decision scale. Analysis of the data used Spearman Rho?s non parrametric statistics. The result of this study revealed that emotional readinnes positively correlated with marital decision and career oriented negatively correlated with marital decision. Both of emotional readinnes and career oriented has influenced decision marital